2021
DOI: 10.3390/molecules26164782
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cluster Size on the Intra-Cluster Ionic Polymerization Process

Abstract: Polyaromatic hydrocarbons (PAHs) are widespread in the interstellar medium (ISM). The abundance and relevance of PAHs call for a clear understanding of their formation mechanisms, which, to date, have not been completely deciphered. Of particular interest is the formation of benzene, the basic building block of PAHs. It has been shown that the ionization of neutral clusters can lead to an intra-cluster ionic polymerization process that results in molecular growth. Ab-initio molecular dynamics (AIMD) studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Here, we focus on reactions of hydrocarbons with oxygen in its singlet form, O( 1 D). A possible explanation for the difference in the products in the gas phase and the ice environment is that the molecules in the ice alter the potential energy surfaces (PES) as observed previously in the case of molecular clusters [25,26,50,51]. However, stability analysis of the different products on the PES reveals that while changes in stability were observed, they do not significantly alter the PES, as demonstrated in Appendix A.…”
Section: Introductionmentioning
confidence: 79%
“…Here, we focus on reactions of hydrocarbons with oxygen in its singlet form, O( 1 D). A possible explanation for the difference in the products in the gas phase and the ice environment is that the molecules in the ice alter the potential energy surfaces (PES) as observed previously in the case of molecular clusters [25,26,50,51]. However, stability analysis of the different products on the PES reveals that while changes in stability were observed, they do not significantly alter the PES, as demonstrated in Appendix A.…”
Section: Introductionmentioning
confidence: 79%
“…The importance of intermolecular forces in the ionic polymerization process on large clusters of acetylene molecules to form polyaromatic hydrocarbons (PAHs) has been studied by Molina and Stein [ 9 ]. They employed ab initio molecular dynamics (AIMD) simulations within interstellar medium (ISM) conditions and showed that four acetylene units can aggregate to form C 8 -bonded species, some of which are bicyclic structures.…”
mentioning
confidence: 99%